The COVID-19 health crisis and its impact on China's international relations - Jean-Pierre Cabestan (Journal of Risk and Financial Management, 2022)
Using qualitative methods, this article focuses on the relationship between the COVID-19 health crisis and China's foreign policy and foreign relations. My main argument is that since its outbreak in late 2019, the COVID-19 health crisis has deepened the tensions already existing between China and the United States, as well as China and the West in general. Other factors that appeared before the pandemic have also contributed to intensifying the Sino-US rivalry as well as Sino-European frictions. Nonetheless, Beijing's proactive mask and vaccine diplomacy, its strict lockdown policy as well as its more aggressive nationalist and anti-western narrative have fed rather than alleviated these tensions. While China's image in the Global South has remained largely positive, in the Global North, it has rapidly deteriorated. All in all, this paper demonstrates that the pandemic has been an aggravating factor contributing to the downward spiral of China's relations with the outside world as well as its own isolation.
Keywords: 330; COVID-19; China; United States; European Union; Xi Jinping; Donald Trump; Joe Biden